Evaluating nivolumab plus gemcitabine–cisplatin’s cost-effectiveness for aUC in China - Meng, Kehui; Xiang, Heng; Wu, Meiyu; Xie, Ouyang; Li, Andong; Tan, Chongqing; Wan, Xiaomin (Frontiers in Pharmacology, 2024)
Aims Assessing the cost-effectiveness of Nivolumab with Gemcitabine–Cisplatin for Advanced Urothelial Carcinoma (aUC) treatment from the perspective of Chinese payers. Methods A Markov model assessed economic outcomes, estimating health outcomes in quality-adjusted life years (QALYs). One-way and probabilistic sensitivity analyses were conducted to assess the impact of uncertainties on the results. Results The base-case analysis showed Nivolumab plus Gemcitabine–Cisplatin yielded 0.59 QALYs at an extra cost of $78,780.61, leading to an incremental cost-effectiveness ratios (ICER) of $133,526.46/QALY. One-way sensitivity analysis highlighted Nivolumab’s cost as the key factor, while probabilistic sensitivity analysis showed a 0% chance of cost-effectiveness for Nivolumab plus Gemcitabine–Cisplatin in aUC treatment. Conclusion Nivolumab plus Gemcitabine–Cisplatin is not cost-effective in the treatment of aUC.